2018
DOI: 10.1002/admi.201800189
|View full text |Cite
|
Sign up to set email alerts
|

Folding of Nanoparticle Chains into 2D Arrays: Structural Change of DNA‐Functionalized Gold Nanoparticle Assemblies

Abstract: Nanoparticle (NP) arrays exhibit collective physical and chemical properties, which are potentially applicable to various nanodevices, such as data storage media and biosensors. In this Communication, a spontaneous method of constructing the 2D NP arrays from precursory 1D chains of DNA‐modified NPs is described. The single‐stranded (ss) DNA‐modified gold NPs are hybridized to a long repetitive ssDNA synthesized with rolling circle amplification to produce the precursory NP chains. Transmission electron micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 63 publications
0
14
0
Order By: Relevance
“…When the fully matched DNA duplexes were formed on the particle surfaces, the TEM observation revealed highly packed 2D AuNP assemblies (Figures e and S2). This result was consistent with our previous study employing linear AuNP assemblies . The average number of AuNPs per assembly (Figure h) was in good agreement with the value for the precursory ssDNA–AuNP assembly (Figure g).…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…When the fully matched DNA duplexes were formed on the particle surfaces, the TEM observation revealed highly packed 2D AuNP assemblies (Figures e and S2). This result was consistent with our previous study employing linear AuNP assemblies . The average number of AuNPs per assembly (Figure h) was in good agreement with the value for the precursory ssDNA–AuNP assembly (Figure g).…”
Section: Resultsmentioning
confidence: 85%
“…In contrast, the particles having a single-base mismatch or a single-nucleotide overhang on the periphery of the DNA shell continue to stably disperse. In a previous study, we prepared a precursory linear chain of fully matched dsDNA–AuNPs using a long repetitive DNA strand as a template . By inducing non-cross-linking assembly between the constituent particles, the chains were folded to afford 2D arrays of AuNPs on the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…For AuNSs that exhibit uniform surface activity, however, it would be much more difficult, even though a multi-step method has been used to prepare bifunctional monomer to construct assemblies with ordered spatial arrangement. [56][57][58][59][60]…”
Section: Analytical Sciencesmentioning
confidence: 99%
“…Over the past two decades, control of the nanomaterial assembly mediated by DNA strands has been widely used in both fundamental and applied research, owing to excellent programmability and selectivity. In most cases, nanomaterials were designed to crosslink each other via the formation of a duplex between the surface-immobilized DNA strands on assembling. Maeda and co-workers demonstrated that nanoparticles densely covered with oligo-DNA strands (DNA-NPs) aggregate in aqueous salt solutions without crosslinking formation; they showed that DNA-NPs can be dispersed stably even under high-salt conditions, but the fully matched duplex formation with complementary DNA strands on the surface leads to spontaneous aggregation in a noncrosslinking manner. Interestingly, no aggregation occurred under the same high-salt conditions when the resulting duplex terminal was a single-base mismatch or overhang sequence. Such terminal sequence-specificity in the dispersion behavior of DNA-NPs has been used not only for analytical purposes such as the detection of genetic polymorphisms/mutations, , toxic metal ions, , and more , but also for the construction of nanomaterial assemblies with dynamic functions. …”
Section: Introductionmentioning
confidence: 99%